Digital health tools and habit formation: Investigating the role of anti-addiction systems in mitigating social media dependency - Xu, Jiangmeiling (International Journal of Innovative Research and Scientific Studies, 2025)
The pervasive use of social media has raised global concerns about digital addiction, prompting technology companies to develop anti-addiction systems as part of digital health tools. This mixed-methods empirical study investigates the effectiveness of these systems in mitigating social media dependency, combining quantitative surveys (N=189) and qualitative interviews. Results reveal a significant gap between tool availability and user engagement: only 25% of participants actively used anti-addiction features, while 75% ignored or circumvented them. Despite initial reductions in screen time, long-term efficacy remains limited, particularly among adolescents who exploit technical loopholes (e.g., parental ID binding). Thematic analysis highlights that current systems prioritize short-term restrictions over habit-forming strategies, failing to address intrinsic motivations such as boredom gratification (70%) and social validation (36.67%). Age-specific disparities are evident, with younger users (14–18 years) demonstrating higher resistance to interventions. The study underscores the need to integrate behavioral science principles—such as personalized feedback and gamified rewards—into anti-addiction designs to foster sustainable behavior change. These findings challenge the efficacy of purely technical solutions, advocating for interdisciplinary approaches that bridge digital tools, psychological incentives, and developmental needs.